Fabrication and evaluation of BerNPs regarding the growth and development of Streptococcus mutans - Nguyen, Tuyen Huu; Pham, Hong Thanh; Nguyen, Kieu Kim Thanh; Ngo, Loan Hong; Mai, Anh Ngoc Tuan; Lam, Thu Hoang Anh; Phan, Ngan Thi Kim; Pham, Dung Tien; Hoang, Duong Thuy; Nguyen, Thuc Dong; Truong, Lien Thi Xuan (Beilstein Journal of Nanotechnology, 2025)
In this study, berberine nanoparticles (BerNPs) were prepared using a wet-milling method with zirconium balls to enhance bioavailability and expand potential applications. The particle size and physicochemical properties of the BerNPs were analyzed using field-emission scanning electron microscopy (FE-SEM), UV–vis spectroscopy, X-ray diffraction, and Fourier-transform infrared spectroscopy. The broth dilution method was used to determine the antimicrobial activity of the BerNPs against Streptococcus mutans (S. mutans). The impact of the BerNPs on the cell surface of S. mutans was evaluated through FE-SEM analysis, focusing on its ability to inhibit biofilm formation. The results demonstrated that BerNPs were produced with an average particle size of 40–65 nm. The chemical structure of BerNPs remained consistent with that of berberine, with no modifications occurring during nanoparticle preparation. The BerNPs exhibited the ability to inhibit S. mutans, with minimum inhibitory concentration and minimum bactericidal concentration values of 78.1 and 312.5 µg/mL, respectively. BerNPs caused significant damage to S. mutans cells, disrupting the cell membrane structure, and leading to cell lysis and death. Additionally, BerNPs effectively inhibited the biofilm formation of S. mutans. In summary, BerNPs demonstrated a potent inhibitory effect on the activities of S. mutans at selectively applied concentrations.
Keywords: antibacterial; berberine nanoparticles; BerNPs; biofilm; FE-SEM; Streptococcus mutans